Technology Acceptance Model in Socrative as a Learning Grammar Software: Higher Education Students’ Perception - Daulay, Sholihatul Hamidah; Nabila, Afanin; Nst, Ahmad Husein; Ningsih, Fitri Randia; Perkasyah, Musthafa Fadli (Linguistics and ELT Journal, 2023)
Technological advancement that are happening today provide many conveniences, including in the world of education, especially teaching writing. The main objective of this research is to find out how students perceive the use of Socrative to teach English grammar. The method used in this research is descriptive qualitative. Students enrolled in the second semester of the English Education Study Program for the 2022–2023 academic year are the participants. Interviews and questionnaires were used to collect data for this investigation. The questionnaire included 20 (twenty) items regarding perceived utility and perceived ease of use, which the  technology acceptance model (TAM) theory has developed to ensure the reliability and validity of the questionnaire. The findings of this research indicated that students have a very good evaluation of the use of social constructions in teaching grammar. The results proved that they accept the application of Socrative well in their learning process